Analisis Faktor Kepatuhan Tenaga Kesehatan terhadap Vaksinasi Influenza A di Asia: Tinjauan Naratif - Suryoadji, Kemal Akbar; Wardani, Arimbi Kusuma; Setyawan, Dhanis Adrianto; Faruqi , Muhammad; Susilo , Adityo; Pohan , Herdiman T. (Medical : Jurnal Kesehatan dan Kedokteran, 2025)
Influenza A is a contagious respiratory disease with a high global burden, causing 3–5 million severe cases and up to 650,000 deaths annually. Healthcare workers have a higher risk of infection, especially if unvaccinated, which increases the likelihood of transmitting the virus to vulnerable patients. Although the WHO recommends annual vaccination, global coverage remains low (41.7%) and is even lower in Asia (28.5%). This narrative review synthesizes demographic, psychosocial, and institutional factors influencing influenza A vaccination compliance among healthcare workers in Asia. Literature searches were conducted in PubMed, Scopus, and Google Scholar for English- or Indonesian-language articles published from 2020 to 2025. Four primary studies met the inclusion criteria, all originating from China. Vaccination coverage among healthcare workers varied widely (1.36%–67.5%), while willingness to vaccinate was generally higher. Facilitating factors included increased risk perception, confidence in vaccine safety and effectiveness, and easy access to vaccines. Barriers included vaccine cost, safety concerns, low personal risk perception, insufficient information or training, and limited institutional support. Influenza A vaccination compliance among healthcare workers in Asia remains low and is influenced by a combination of individual and institutional factors. Multidimensional interventions, such as providing free vaccines, offering vaccination facilities in the workplace, enhancing education, and implementing strong institutional policies, are needed to improve vaccination coverage.